Relationship of Spirituality Leadership Practice among Food and Beverage SMEs Manufacturers in Halal Supply Chain - Mohamed Elias, Ezanee; M, Norlila; Othman, Mohamad Zainudin; Abu Bakar, Siti Zakiah; Khalid, Kamal (ExcelingTech, 2020)
The influence of a company's leadership on the business, especially those involved in the halal food and beverage industry in Malaysia. Therefore, it is the intention of this study to examine the relationship of the spirituality leadership towards halal business in food industry which is growing rapidly among the SME manufacturers. To achieve the study’s objective, a conceptual framework is proposed via in-depth literature review. This study uses quantitative methods utilising data collection through online questionnaires. A total of 187 respondents from top management answered the questions within a three months span. The data obtained were analyzed with SPSS software. This study presents a hypothesis with three elements and the results has shown that all hypothesis are supported. There is a significant relationship between the spirituality leadership adoption and the halal business with r value of 0.762. As a conclusion, the results of the study can be an informative model for future leaderships implementation of spirituality mainly for halal SMEs businesses in Malaysia.